Study of Structure of Industrial Acid Hydrolysis Lignin, Oxidized in the H2O2-H2SO4 System. (3rd July 2016) - Evstigneyev, Edward I.; Yuzikhin, Oleg S.; Gurinov, Andrey A.; Ivanov, Alexandr Yu.; Artamonova, Tatiana O.; Khodorkovskiy, Mikhail A.; Bessonova, Elena A.; Vasilyev, Aleksander V.
Abstract : Products of oxidation of industrial acid hydrolysis lignin in the H2 O2 -H2 SO4 system were studied using 13 C NMR (in solution and solid state), MALDI-MS, and MS(ESI) techniques. Oxidation of hydrolysis lignin leads to the opening of aromatic rings of lignin, yielding carboxylic groups. Alkyl aryl ether linkages (β-O-4-bonds) between lignin phenyl propane units are not significantly affected by the oxidation. The structure of oxidized hydrolysis lignin is proposed. The basic structural unit of oxidized hydrolysis lignin is a muconic acid derivative.